2008
DOI: 10.1007/s10548-008-0058-1
|View full text |Cite
|
Sign up to set email alerts
|

EEG and fMRI Coregistration to Investigate the Cortical Oscillatory Activities During Finger Movement

Abstract: Electroencephalography combined with functional magnetic resonance imaging (EEG-fMRI) may be used to identify blood oxygenation level dependent (BOLD) signal changes associated with physiological and pathological EEG event. In this study we used EEG-fMRI to determine the possible correlation between topographical movement-related EEG changes in brain oscillatory activity recorded from EEG electrodes over the scalp and fMRI-BOLD cortical responses in motor areas during finger movement. Thirty-two channels of EE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 37 publications
4
37
0
Order By: Relevance
“…This asymmetric pattern of activation is in line with previous results showing left-lateralized power decrease during the reading of hand verbs [39] and covert verb generation [38]. Under the assumption that beta suppression represents neural activation [54], [55], [56], our findings also agree with those from fMRI studies showing left-lateralized neural activity during action-related language processing [11], [12], [14], [15], [16]. Consistently, inhibition of reaction times during the processing of hand action verbs was induced with TMS on the left, but not on the right hemispheric hand portion of the motor cortex [57].…”
Section: Discussionsupporting
confidence: 92%
“…This asymmetric pattern of activation is in line with previous results showing left-lateralized power decrease during the reading of hand verbs [39] and covert verb generation [38]. Under the assumption that beta suppression represents neural activation [54], [55], [56], our findings also agree with those from fMRI studies showing left-lateralized neural activity during action-related language processing [11], [12], [14], [15], [16]. Consistently, inhibition of reaction times during the processing of hand action verbs was induced with TMS on the left, but not on the right hemispheric hand portion of the motor cortex [57].…”
Section: Discussionsupporting
confidence: 92%
“…Localization studies in adults suggest that the alpharange component of the mu rhythm is mainly generated in primary somatosensory cortex [102][103][104]. Furthermore, the adult EEG mu response varies with changes in somatosensory aspects of observed actions [105][106][107], a finding that connects with other work at the intersection of somatosensory processing and social neuroscience [108], including affective aspects [109].…”
Section: Unpacking the Origins And Meaning Of Mu Rhythm Desynchronizamentioning
confidence: 89%
“…It has been shown that SMR-ERD covaries with blood-oxygen-level-dependent (BOLD) signals as measured by magnetic resonance imaging (MRI) deriving from the same cortical areas (Formaggio et al, 2008(Formaggio et al, , 2010Yuan et al, 2010). Studies using transcranial magnetic stimulation (TMS) delivered to the primary motor cortex (M1) have shown that an increase of corticospinal tract excitability is associated with a SMR-ERD decrease (Hummel et al, 2002) and is accompanied with decrease of GABAergic intracortical inhibition (Takemi et al, 2013).…”
Section: Identification Of Biomarkers For Bmi Motor Rehabilitationmentioning
confidence: 99%